Burning water - the state, irrigation technology and the production of scarcity in Spain - Closas Farriol, A (2013)
Through studying the adoption of groundwater abstraction technology in the twentieth century in La Mancha, this research investigates the historical role of the state in the development of modern groundwater-fed irrigation in Spain between the 1940s and 1985. By focusing on the Mancha Occidental aquifer and the Las Tablas de Daimiel wetland, this study also scrutinizes how the adoption of groundwater abstraction technology led by the state fed back into the environment through ecosystem degradation and groundwater scarcity at the local and regional level. By examining the historical links between technology adoption, statecraft and ecological change, this study explores the different ways through which the state has taken a prominent role in producing groundwater-fed irrigation socio-ecologies. Additionally, it traces the socio-political mechanisms involved in the progressive desiccation of the Las Tablas de Daimiel wetland and its transformation into a burning dryland.